Akulturasi Hukum Islam Dan Kearifan Lokal: Kajian Pergeseran Tradisi Sanksi Hukum Adat Kawin Semarga Masyarakat Batak Angkola - Nasution, Ismail; Hasibuan, Nur Hikmah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to examine the shift in the tradition of sanctioning the Semarga Marriage Customary Law in Sibuhuan, Padang Lawas. This research is qualitative research by identifying the existence of factors that cause clan marriages to occur and customary sanctions for perpetrators of clan marriages in the community in Sibuhuan. The results of the research show that the factors that cause clan marriages to occur in Sibuhuan are caused by two factors, namely the influence of Islamic religious teachings which do not prohibit clan marriages, but there are special rules in marriage according to Islam who cannot marry. In general, the perpetrators of clan marriages choose the rules. according to the teachings of Islam. Meanwhile, the second factor is due to the lack of understanding of the people in Sibuhuan about Batak customs which do not allow marriage within the clan because it will have an impact on Batak traditions. Meanwhile, there are several types of customary sanctions for perpetrators of marriage with the same clan, namely, (1) customary sanctions for prospective parents-in-law; (2) A woman who is married to her husband's surname must change her surname by asking for the surname from the husband's mother through the Adat process; (3) The surname of the groom's mother must be given to the bride and only applies to herself; (4) If there is a male child in their offspring in the future, the male child is not permitted to take bone boru and (5) cannot take part in the traditional banquet served at anyone's wedding party, before doing these four things. The conclusion obtained from this research is that intermarriage often occurs because the Angkola Batak community in Sibuhuan prioritizes religious teachings over customs and lacks understanding of Western customs. Then the traditional sanctions against perpetrators of intermarriage in the Angkola Batak Community in Sibuhuan still exist today, although they are not too heavy for the perpetrators.